Memo - of Gowers Interview, Miners' Federation of Great Britain (page 1) (1926)
1926-12-31 "Memo - of Gowers Interview, Miners' Federation of Great Britain (page 1)" [g0527001.jpg], 1926, Miners' Federation of Great Britain The Return to Work